Protection of the environment in times of international armed conflict - Zaki, Maria Mohammed Mahmoud (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aims to identify the most important international principles for protecting the environment in times of armed conflict, Whereas the environment is an ecosystem that consists of an interconnected group that differs in size and type of organisms and organic and inorganic elements that are balanced in a relatively stable manner. Since man is one of the most important living creatures, which necessitates human protection to preserve the environment and its balance, the international community has set controls for the use of military force, since wars are an inevitable evil, Among the most important of them is the principle of balance between military necessity and humanitarian considerations. And we used the analytical method in the study by analyzing and studying the principles of international humanitarian law. And from the above, we divided the study into three demands, the first demands dealt with the concept of military necessity in international humanitarian law, while we discussed in the second demands the concept of the principle of balance in international humanitarian law, and in the third demands we dealt with the principle of balance between military necessity and humanitarian considerations. One of the most important findings of this study is that the principle of military necessity protects the natural and civilian environment through its association with the principle of humanity, which constitute the principle of balance between military necessity and humanitarian considerations, The principle of balance between military necessity and humanitarian considerations regulates the use of weapons during armed conflicts and prohibits the use of weapons of mass destruction to protect the environment during armed conflicts. The researcher recommends that the United Nations Organization renew international agreements prohibiting the use of weapons of mass destruction in line with modern science and developments in scientific fields.
Keywords: environment; military necessity; humanitarian considerations